(untitled) (International Journal of Physiotherapy, 2025)
Background: Hypertension is a significant risk factor for cardiovascular disease (CVD) in postmenopausal women. The decline in estrogen levels during menopause contributes to increased oxidative stress, endothelial dysfunction, and heightened sympathetic activity, all of which can elevate blood pressure. Various approaches, including pharmacological and nonpharmacological interventions, are utilized to manage hypertension, with aerobic exercise being a recommended strategy for both prevention and treatment. However, limited research directly compares the effects of interval and continuous aerobic training on blood pressure in hypertensive postmenopausal women. This study aimed to assess the effectiveness of moderateintensity continuous aerobic training and high-intensity interval aerobic training in reducing blood pressure and body mass index (BMI) in this population. Methods: This experimental study included 30 postmenopausal women diagnosed with Stage 1 hypertension, randomly assigned to three groups: Group A (moderate-intensity continuous aerobic training), Group B (high-intensity interval aerobic training), and Group C (control group). The intervention lasted six weeks, with training sessions conducted thrice weekly. Blood pressure and BMI were recorded before and after the intervention. Data analysis involved ANOVA and post-hoc tests to examine intra-group and inter-group differences. Results: Both Group A and Group B showed a significant reduction in systolic and diastolic blood pressure (p<0.05). Group B demonstrated a more significant decrease in systolic blood pressure (from 142.7 ± 5.1 mmHg to 127.7 ± 4.6 mmHg, p<0.05) compared to Group A (from 140.7 ± 4.4 mmHg to 135.2 ± 4.3 mmHg, p<0.05). Similarly, diastolic blood pressure was significantly lower in Group B (from 91.0 ± 3.5 mmHg to 81.7 ± 3.5 mmHg, p<0.05) compared to Group A (from 92.3 ± 3.0 mmHg to 88.5 ± 2.7 mmHg, p<0.05). BMI reduction was also more pronounced in Group B (from 27.3 ± 1.5 kg/m² to 25.3 ± 1.4 kg/m², p<0.05) than in Group A (from 27.4 ± 1.7 kg/m² to 26.6 ± 1.6 kg/m², p<0.05). No significant changes were observed in Group C. Conclusion: Both training methods effectively reduced blood pressure and BMI in hypertensive postmenopausal women. However, high-intensity interval training significantly reduced systolic and diastolic blood pressure and BMI more than moderate-intensity continuous training. These findings highlight the potential of interval training as a more efficient approach for managing hypertension in postmenopausal women.